HUBUNGAN KADAR ZINK SERUM DENGAN DERAJAT NEUROPATI DIABETIK - Udi Panata; Dodik Tugasworo; Amin Husni (NEURONA, 2019)
THE ASSOCIATION BETWEEN SERUM ZINC LEVELS AND SEVERITY OF DIABETIC NEUROPATHYABSTRACTIntroduction: Diabetic neuropathy (DN) is one of the complications in diabetes mellitus (DM) that occurs frequently. This might be caused by deficiencies of trace elements, such as zinc, related to the complications. Zinc controls hyperglycemic factor and oxidative stress caused by hyperglycemia, which causes DN.Aim: To analyze the association between serum zinc levels and severity of DN in patients with type 2 DM.Methods: An observational analytical study with cross-sectional approach was conducted. Sixty subjects diagnosed with type 2 DM in the Neurology Clinic of Dr. Kariadi General Hospital, Semarang and HM Ashari General Hospital, Pemalang were scored using Toronto Clinical Scoring System (TCSS) to measure severity of DN. Characteristic data were analyzed descriptively. Categorical analysis were analyzed using Mann-Whitney method. The variables were also analyzed using Mann-Whitney test and unpaired t-test between Semarang and Pemalang Hospitals. Furthermore, all variables were tested for multivariate analysis using linear regression.Results: There were 60 subjects with a majority of females (63.3%) who suffer from DN (90%) and of 52.35±4.02 years old in age with duration of disease of 9.37±3.44 years. On average, the serum zinc levels were found normal, while average triglyceride and HbA1c levels were increased. It was observed that there were correlations among DN severity, serum zinc levels, duration of DM disease and serum triglyceride levels. In multivariate data analysis, the most significant relationship was found between triglyceride levels and duration of DM disease.Discussion: Hyperglycemia causes glucose accumulation in nerve tissues. In a long period of time, high blood glucose levels will damage the blood vessels walls that are directly related to nerves. Furthermore, in elderly patients, the amount of blood flow to peripheral nerves decreases. High triglyceride levels becomes a predictive factor that severely decreases myelin nerve fibers density. Whereas, zinc can prevent the decrease in motor nerve conduction speed.Keywords: DN, serum zinc levels, type 2 DMABSTRAKPendahuluan: Neuropati diabetik (ND) adalah salah satu komplikasi diabetes melitus (DM) yang lebih sering terjadi. Hal ini dapat disebabkan oleh defisiensi trace element akibat komplikasi diabetes, antara lain zink. Elemen ini mengendalikan faktor hiperglikemik dan stres oksidatif yang disebabkan oleh hiperglikemia, hingga menyebabkan ND.Tujuan: Menganalisis hubungan kadar zink serum dengan derajat ND pada pasien DM tipe 2, dan faktor-faktor lain yang memengaruhinya.Metode: Penelitian analitik observasional secara potong lintang terhadap pasien DM tipe 2 yang berobat di Po- liklinik Penyakit Saraf RSUP Dr. Kariadi, Semarang dan RSUD HM Ashari, Pemalang. Subjek dilakukan pengukuran derajat ND menggunakan Toronto Clinical Scoring System (TCSS). Data karakteristik dianalisis secara deskriptif. Analisis kategorikal menggunakan metode Mann-Whitney, pengujian antar variabel juga dengan Mann-Whitney dan uji t tidak berpasangan, serta uji multivariat menggunakan regresi linear.Hasil: Didapatkan 60 subjek yang mayoritas perempuan (63,3%) dan menderita ND (90%), serta rerata usia 52,35±4,02 tahun dan rerata durasi menderita DM 9,37±3,44 tahun.  Rerata kadar serum zink dalam batas normal, namun rerata kadar trigliserida dan HbA1c meningkat. Didapatkan hubungan antara ND dengan kadar serum zink, durasi penyakit DM, dan kadar trigliserida serum. Dalam analisis data multivariat, hubungan tertinggi ditemukan antara kadar trigliserida dan durasi penyakit DM.Diskusi: Hiperglikemia menyebabkan akumulasi glukosa pada jaringan saraf. Jangka waktu yang cukup lama, kadar glukosa dalam darah akan merusak dinding pembuluh darah kapiler yang berhubungan langsung ke saraf, ditambah lagi pada usia lanjut terjadi penurunan aliran darah pada pembuluh darah yang menuju saraf tepi. Kadar trigliserida yang tinggi menjadi faktor prediktif penurunan secara dramatis pada masa jenis atau kepadatan serabut saraf mielin. Zink dapat mencegah penurunan kecepatan konduksi saraf motorik.Kata kunci: DM tipe 2, kadar zink serum, neuropati diabetik